2018
DOI: 10.1002/aenm.201800068
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reversible Na Storage in Na3V2(PO4)3 by Optimizing Nanostructure and Rational Surface Engineering

Abstract: Sodium‐ion batteries (NIBs) have attracted more and more attention as economic alternatives for lithium‐ion batteries (LIBs). Sodium super ionic conductor (NASICON) structure materials, known for high conductivity and chemical diffusion coefficient of Na+ (≈10−14 cm2 s−1), are promising electrode materials for NIBs. However, NASICON structure materials often suffer from low electrical conductivity (<10−4 S cm−1), which hinders their electrochemical performance. Here high performance sodium storage performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
113
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(121 citation statements)
references
References 43 publications
4
113
0
Order By: Relevance
“…Figure b displays the XRD spectrum of the NVP@NC composite. The characteristic diffraction peaks of NVP are placed at 14.14°, 19.14°, 23.66°, 28.62°, 31.90°, and 35.5°, corresponding to (012), (104), (113), (024), (114), and (300) surfaces, respectively . The characteristic peaks of the NVP@NC composite are sharp and correspond exactly to the standard card (JCPDS 53‐0018), indicating that the purity of crystal of the NVP material and N‐doped carbon coating is amorphous or content is very small.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Figure b displays the XRD spectrum of the NVP@NC composite. The characteristic diffraction peaks of NVP are placed at 14.14°, 19.14°, 23.66°, 28.62°, 31.90°, and 35.5°, corresponding to (012), (104), (113), (024), (114), and (300) surfaces, respectively . The characteristic peaks of the NVP@NC composite are sharp and correspond exactly to the standard card (JCPDS 53‐0018), indicating that the purity of crystal of the NVP material and N‐doped carbon coating is amorphous or content is very small.…”
Section: Resultsmentioning
confidence: 73%
“…However, the intrinsic properties of these materials, such as serious capacity decay and voltage platform receding because of structural variations during Na + ‐intercalation/removal process or occurring the side reaction, hinder their application in SIBs. Compared with them, Na 3 V 2 (PO 4 ) 3 (NVP) with NASICON structure and higher theoretical specific capacity is considered as an ideal cathode material for SIBs . In addition, its stable 3D host framework brings about thermal stability and ultralong cycle life, although the low electronic conductivity of NVP causes inferior rate character, which limits its utilization .…”
Section: Introductionmentioning
confidence: 99%
“…Na 3 V 2 (PO 4 ) 3 (NVP), with a super ionic conductor framework, is regarded as one of the most promising candidate cathodes due to its high reversible capacity, excellent thermal stability, and fast Na‐ion diffusion tunnel . Furthermore, Na‐ion superionic conductor (NASICON)‐type NVP exhibits a suitable voltage plateau located at 3.4 V versus Na/Na + , correlated with the V 3+ /V 4+ redox couple, and the high theoretical energy density (400 W h kg −1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Therefore, it is always imperative to exploit high performance electrode materials with excellentr ate performance and cycling stability forS IBs, in order to meet the requiremento fc ommercialization. [22,25,[31][32][33][34][35][36][37][38][39] For example,S ong et al [24] reported the synthesis of thin-layer graphene-encapsulated NVP nanoparticles with about 100 nm, whiche xhibited optimized rate performance with discharge capacityo f7 0.1 mAh À1 g À1 at 30 Ca nd enhanced cyclings tability with about 86.0 %c apacity retention at 5Cafter 300 cycles. [13,14] Among variousc athode candidates, such as sodium-based layered metalo xides, [15,16] phosphates, [17,18] andP russian blue analogs (PBAs), [19] NASICON-type Na 3 V 2 (PO 4 ) 3 (denoted as NVP) has been considered as ap romising candidate because of the high theoretical specific capacity,e xcellent thermala nd structural stability.…”
mentioning
confidence: 99%
“…[13,14] Among variousc athode candidates, such as sodium-based layered metalo xides, [15,16] phosphates, [17,18] andP russian blue analogs (PBAs), [19] NASICON-type Na 3 V 2 (PO 4 ) 3 (denoted as NVP) has been considered as ap romising candidate because of the high theoretical specific capacity,e xcellent thermala nd structural stability. [22,25,[31][32][33][34][35][36][37][38][39] For example,S ong et al [24] reported the synthesis of thin-layer graphene-encapsulated NVP nanoparticles with about 100 nm, whiche xhibited optimized rate performance with discharge capacityo f7 0.1 mAh À1 g À1 at 30 Ca nd enhanced cyclings tability with about 86.0 %c apacity retention at 5Cafter 300 cycles. [28][29][30] However,t he intrinsicl ow electronic conductivity results in poor rate performance and unsatisfactory cycle life, whichs eriously impedes its practical application.…”
mentioning
confidence: 99%